The intergenerational mortality tradeoff of COVID-19 lockdown policies - MA, Lin (Institutional Knowledge at Singapore Management University, 2022)
In lower-income countries, the economic contractions that accompany lockdowns to contain COVID-19 transmission can increase child mortality, counteracting the mortality reductions achieved by the lockdown. To formalize and quantify this effect, we build a macro-susceptible-infected-recovered model that features heterogeneous agents and a country-group-specific relationship between economic downturns and child mortality and calibrate it to data for 85 countries across all income levels. We find that in some low-income countries, a lockdown can produce net increases in mortality. The optimal lockdown that maximizes the present value of aggregate social welfare is shorter and milder in poorer countries than in rich ones.